Teachers readiness towards reproductive and social health education - Zainal Abidin, Muhamad Zaiful; Mohd Nasiruddin, Nasnoor Juszaily; Samsudin, Shamsulariffin (Human Resource Management Academic Research Society, 2022)
Sexual education has become a big issue in Malaysia over time since the country faces the highest number of sexually active teenagers. This sensitive issue causes the teaching process to become incomplete, lack of depth and insufficient. Teachers' readiness is essential in acknowledging curriculum reform, such as the Reproductive and Social Health Education (PEERS) curriculum. In general, the purpose of this study is to determine the level and correlation between Health Education (HE) teacher readiness in teaching PEERS curriculum in terms of content knowledge, pedagogical knowledge, and teacher attitudes. A quantitative approach with a survey method was used in this study. The selection sample was conducted by proportionate stratified random sampling involving a total of 354 HE teachers in Selangor secondary schools. The readiness of teachers in teaching the PEERS curriculum showed that the level of attitude is the highest value with a mean score of 4.05 followed by the level of content knowledge with a mean score of 4.00 and the last is the level of pedagogical knowledge with a mean score of 3.96. In addition, there is a significant positive and high-impact correlation between the level of content knowledge, pedagogical knowledge and attitudes toward teacher readiness. The study on teachers' willingness to teach the PEERS curriculum is expected to benefit teachers teaching HE in the Malaysia Education system. This study gives the impression that teachers should be prepared mentally and physically to face challenges in implementing the new curriculum. This study can be used as a reference by the Ministry of Education Malaysia (MOE) to improve the quality of education and improve existing programs.